2001
DOI: 10.1076/apab.109.4.357.4249
|View full text |Cite
|
Sign up to set email alerts
|

NGF, BDNF, Leptin, and Mast Cells in Human Coronary Atherosclerosis and Metabolic Syndrome

Abstract: While multiple growth factor, cytokines, and immune cells are identified in atherosclerotic lesions, as well as an essential nonneuronal function of neurotrophins implicated in cardiovascular tissue development and in lipid and glucose metabolism, the role of the neurotrophins NGF and BDNF and also the adipokine leptin in human coronary atherosclerosis and related disorders, such as metabolic syndrome, remains unclear. Here we report that (i) both the amount and the immunoreactivity of NGF was reduced and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(22 citation statements)
references
References 5 publications
2
20
0
Order By: Relevance
“…All in all, essentially similar results were noted in two different European populations, and, thus, the results seem to be independent of environmental and cultural differences between Northern and Southern Europe. Our results are also in line with studies reporting that mast cells are more abundant in the abdominal subcutaneous adipose tissue in persons with the metabolic syndrome [13] and in obese persons [12]. In the latter study, it was also shown that in mice active mast cells were necessary for a high weight gain [12].…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…All in all, essentially similar results were noted in two different European populations, and, thus, the results seem to be independent of environmental and cultural differences between Northern and Southern Europe. Our results are also in line with studies reporting that mast cells are more abundant in the abdominal subcutaneous adipose tissue in persons with the metabolic syndrome [13] and in obese persons [12]. In the latter study, it was also shown that in mice active mast cells were necessary for a high weight gain [12].…”
Section: Discussionsupporting
confidence: 81%
“…One study investigating ST after acute coronary syndromes did not find elevated ST levels [14], but concluded that the numbers of mast cells activated in the coronary arteries probably were too few to detect a systemic increase in ST. However, the studies on this subject have included a limited number of patients [12,13,14]. A Spanish general population study [15] in 420 adults found that increasing ST levels were associated with increasing BMI and the metabolic syndrome, but these associations were not statistically significant after adjustment for potential confounders.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…BDNF appears to be a primary neuroimmune mediator involved in the development of cardiovascular disease and related disorders [61,62,63]. These data suggest that BDNF may mediate the effect of exercise in decreasing the risk of these diseases as depicted by pathway 2 (fig.…”
Section: Proposed Mechanismmentioning
confidence: 94%
“…Circulating BDNF levels are reduced in patients with metabolic syndrome and in those with an acute coronary syndrome. Conversely, it is possible that increased BDNF levels may buffer against these diseases and reduce allostatic load, but the causal direction is uncertain [63,64] (table 1). Reduced availability of a neurotrophin, such as BDNF, may result in a metabotrophic deficit and explain the pathogenesis of obesity and related metabolic diseases, such as metabolic syndrome, type 2 diabetes, and atherosclerosis [62].…”
Section: Proposed Mechanismmentioning
confidence: 99%